2011
DOI: 10.1371/journal.pone.0021583
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sensitivity to DZNep Induced Apoptosis in Multiple Myeloma Cells

Abstract: The 3-Deazaneplanocin A (DZNep), one of S-adenosylhomocysteine (AdoHcy) hydrolase inhibitors, has shown antitumor activities in a broad range of solid tumors and acute myeloid leukemia. Here, we examined its effects on multiple myeloma (MM) cells and found that, at 500 nM, it potently inhibited growth and induced apoptosis in 2 of 8 MM cell lines. RNA from un-treated and DZNep treated cells was profiled by Affymetrix HG-U133 Plus 2.0 microarray and genes with a significant change in gene expression were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
8
22
0
Order By: Relevance
“…Consistent with our previous reports in which adhesion-mediated signals from fibronectin-engaged VLA-4 play critical roles in the establishment of CAM-DR in MM cells (17, 18), Figure 4E). This is compatible with previous studies showing that it was not DZNep, but chaetocin, that exerted significant cytotoxicity against MM cells (19,20). Furthermore, we examined the effects of EZH2 knockdown on anti-MM drug-induced cytotoxicity because H3K27 trimethylation was mainly catalyzed by EZH2.…”
Section: Resultssupporting
confidence: 87%
“…Consistent with our previous reports in which adhesion-mediated signals from fibronectin-engaged VLA-4 play critical roles in the establishment of CAM-DR in MM cells (17, 18), Figure 4E). This is compatible with previous studies showing that it was not DZNep, but chaetocin, that exerted significant cytotoxicity against MM cells (19,20). Furthermore, we examined the effects of EZH2 knockdown on anti-MM drug-induced cytotoxicity because H3K27 trimethylation was mainly catalyzed by EZH2.…”
Section: Resultssupporting
confidence: 87%
“…by guest www.bloodjournal.org From compound capable of depleting PRC2 components called DZNep. 31 As reported previously, [31][32][33][34] DZNep effectively and dose-dependently reduced cellular levels of EZH2 in KHYG1 and NKYS, resulting in apoptosis as detected by PARP cleavage using western blot and Annexin V analysis by flow cytometry in a dose-dependent manner ( Figure 6A,C). At the same time, CCND1 is downregulated by DZNep at both the mRNA and protein levels ( Figure 6A-B).…”
Section: Inhibition Of Ezh2 By 3-deazaneplanocin a (Dznep) Induced Grsupporting
confidence: 75%
“…Although DZNep exhibits promising antitumor effects, emerging evidence suggests that specific molecular factors determine the DZNep response or resistance in different tumors. For example, it has been reported that ALOX5 levels may contribute to DZNep sensitivity in multiple myeloma cells (24). Moreover, estrogen receptor-negative breast cancers with low BRCA1 levels may be particularly sensitive to DZNep (25).…”
Section: Discussionmentioning
confidence: 99%